2007
DOI: 10.5694/j.1326-5377.2007.tb00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevocational medical training and the Australian Curriculum Framework for Junior Doctors: a junior doctor perspective

Abstract: The current system of prevocational training does not meet the needs of junior doctors because of a high administrative workload, insufficient funding for education, and a lack of centralised guidance for trainees, teachers and hospitals. The Australian Curriculum Framework for Junior Doctors is designed to identify the training objectives for the prevocational years. The Framework has the potential to improve the quality of training of junior doctors, but this depends on how well it is implemented and resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…It is generally assumed that interns are able to perform basic core skills, such as U/C under supervision when first entering the workplace 17. However, our previous study found that immediately prior to the commencement of internship, almost one-third (29%) of Pre-Intern (PrInt) students had never performed male U/C 18.…”
Section: Introductionmentioning
confidence: 86%
“…It is generally assumed that interns are able to perform basic core skills, such as U/C under supervision when first entering the workplace 17. However, our previous study found that immediately prior to the commencement of internship, almost one-third (29%) of Pre-Intern (PrInt) students had never performed male U/C 18.…”
Section: Introductionmentioning
confidence: 86%
“…The role of junior medical staff in public hospitals is often characterized by a dichotomy between service provision and training 7 . Rather than simply being service providers, junior doctors are acknowledged as ‘doctors in training’ whose learning needs and responsibilities deserve consideration 9,10 . In Australia, State Medical Boards and Postgraduate Medical Councils are responsible for stipulating the training and supervision requirements for interns, the nature of rotations that can and must be taken, and the settings in which they can be undertaken 11–13 .…”
Section: Reviewmentioning
confidence: 99%
“…7 Rather than simply being service providers, junior doctors are acknowledged as 'doctors in training' whose learning needs and responsibilities deserve consideration. 9,10 In Australia, State Medical Boards and Postgraduate Medical Councils are responsible for stipulating the training and supervision requirements for interns, the nature of rotations that can and must be taken, and the settings in which they can be undertaken. [11][12][13] There has, however, been concern regarding lack of uniformity across States, difficulty in identifying common education goals, and inconsistencies in supervision and assessment/feedback.…”
Section: Reviewmentioning
confidence: 99%
“…However, will the Framework make any difference to the educational experience in those transitional years? This is a point of concern for JMOs, as discussed by https://doi.org/10.5694/j.1326-5377.2007.tb00831.x in this issue 7 …”
mentioning
confidence: 96%
“…Assessment may be even harder. Although the JMOs are not keen for assessment to be used for registration, 7 registration is a recognition of a level of competence and needs to involve some form of assessment. How can we be sure that doctors have reached a level of competence where they can be left to care for patients independently or are ready to move to the next stage of training?…”
mentioning
confidence: 99%